IMPLEMENTASI SISTEM INFORMASI KEPEGAWAIAN STIE YPPI REMBANG BERBASIS WEB - Sodiq, Fajar (Program Studi Teknik Informatika Universitas PGRI Ronggolawe, 2021)
Information systems have developed a lot along with the development of Science and Technology in various fields. One of the fields that is greatly affected by the development of science and technology is the world of education. The service and data collection process for STIE YPPI Rembang employees has not yet maximized the use of the data collection system so that employee data collection is still centralized by the administrator, here the role is held by the HR department, so it is less effective and efficient if there is a change in employee data the data is transferred to the HR department. The purpose of the research is to produce a system or application of information systems that are expected to help the HR department and administrators in managing and controlling employee documents. The development of this personnel information system application is web-based and MySQL as the database. The method used is SDLC (System Development Life Cycle) with a waterfall process in the hope that if there is system development it can be easily implemented. Keywords: Service, Personnel Information System, SDLC, Waterfall, Science and Technology.